Fowl Cholera in Chickens: Current Trends in Diagnosis and Phenotypic Drug Resistance in Gondar City, Ethiopia - Abdo Megra Geda (Veterinary Medicine International)
Ethiopia, with an estimated chicken population of 17 million, serves as a source of high-quality animal protein, helping to reduce malnutrition, improve nutritional status, and provide food and food products. However, Ethiopia has not fully leveraged the value of chicken production due to various bacterial diseases, with fowl cholera (FC) being the most common. Therefore, the objective of this review is to highlight the current trends in the diagnosis of FC in chickens and asses its phenotypic drug resistance patterns in Gondar City. FC is an infectious disease caused by Pasteurella multocida (P. multocida), which poses significant health and financial losses to the poultry industry. Culturally, the bacterium P. multocida can be isolated using bacteriological and biochemical tests from chicken infected with FC. Molecular-based techniques such as capsular and lipopolysaccharide genotyping, as well as nucleic acid amplification tests through PCR assays, are also among the best methods used to detect P. multocida. In conclusion, understanding the current trends in diagnosing FC and assessing its phenotyping drug resistance, which helps in choosing effective antibiotics in Gondar City, is essential. It is also important to assess the disease-associated factors that enhance the occurrence of the disease, in addition to providing the disease preventive and control measures and vaccination programs based on the diagnosis of its causative agent.